(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2010)
Internet has made our lives simpler by connecting us to the other parts of the world. World Wide Web, the most important ingredient has helped not only business personnel but also individuals in expressing and sharing their thoughts, ideas, opinions, and facts. It is through the webpage and its technology that one can display the products, prices, features or anything either as text or picture with visual effects, sound and video. This book therefore attempts to integrate the concepts of World Wide Web with the methodology of creation of a website. This book follows the functional approach which is visible from the example under each heading and sub heading. In the first unit of the book, concept of web technology, major characteristics of web, planning your website topics are fully explained. In concept of web technology how www(world wide web) works, domain, IP address, URL (uniform resource locator), internet protocol, HTTP, SMTP/MIME, web caching, web server, proxy server, firewall, scripting languages (HTML, XML, JAVA Scripting), portal, home page, cookies, browsers, search engine, internet & intranet, extranet are fully explained basic tools & techniques which are used to design or to run the website. In major characteristics web server, web browsers, ISP (Internet Service Provider), IIS (Internet information service), internet explorer are fully explained. This shows the important characteristics of web & Internet technology.